Orpheovirus IHUMI-LCC2: A New Virus among the Giant Viruses - Andreani, Julien; Khalil, Jacques Y. B.; Baptiste, Emeline; Hasni, Issam; Michelle, Caroline; Raoult, Didier; Levasseur, Anthony; La Scola, Bernard (Frontiers in Microbiology, 2018)
Giant viruses continue to invade the world of virology, in gigantic genome sizes and various particles shapes. Strains discoveries and metagenomic studies make it possible to reveal the complexity of these microorganisms, their origins, ecosystems and putative roles. We isolated from a rat stool sample a new giant virus “Orpheovirus IHUMI-LCC2”, using Vermamoeba vermiformis as host cell. In this paper, we describe the main genomic features and replicative cycle of Orpheovirus IHUMI-LCC2. It possesses a circular genome exceeding 1.4 Megabases with 25% G+C content and ovoidal-shaped particles ranging from 900 to 1300 nm. Particles are closed by at least one thick membrane in a single ostiole-like shape in their apex. Phylogenetic analysis and the reciprocal best hit for Orpheovirus show a connection to the proposed Pithoviridae family. However, some genomic characteristics bear witness to a completely divergent evolution for Orpheovirus IHUMI-LCC2 when compared to Cedratviruses or Pithoviruses.